POSITION OF A NOTARY IN THE MAKING AND REVOKING OF A WILL (Study at the Notary Office of Herry Aprizal, SH,Sp.N) - Daffaraza Ramadhan; Suwardi (CV. RADJA PUBLIKA, 2025)
Notaries play an important role in the preparation and revocation of wills due to their authority as the official who makes authentic deeds that guarantee legal certainty regarding the testator's last wishes. This study aims to examine the position and duties of notaries in this process through normative and empirical methods, including analysis of regulations, literature, and field data at the Notary Office of Herry Aprizal, SH, Sp.N. The results of the study indicate that notaries are authorized to prepare and store wills and are required to report the preparation, changes, and revocation of wills to the Estates Office and the Central Wills Register. Revocation is only valid if carried out by the maker in a competent state, and the notary must ensure that the procedure meets legal requirements. The study confirms that notary professionalism is a key factor in ensuring legal certainty and order regarding the implementation of wills.